The New Crystal Palace Polka - J. Theodore Trekell::::::::: (Campbell, Ransford & Co.)
Piano score with accompaniment for cornet piston, 5 p. cover title: Dance Music for the New Crystal Palace dedicated to Amelia Agnes Munro of Fowlis Castle, Rosshire on cover is a lithograph in color of the Crystal Palace, Sydenham, by Augs. Butler, printed by Stannard & Dixon.